CYSTADENOMA OF THE PANCREAS A CASE REPORT - Orhan Hayri ELBİR and Canbek SEVEN and Metin ŞAVKILIOĞLU and Musa AKOĞLU and Fuat ATALAY and Mustafa Şerif ONARAN (Turkish Journal of Gastroenterology, 2020)
-